The impact of compound exercises in the development of some of the skills of the players football halls (Journal of the College of Basic Education, 2019)
The importance of the research lies in the design of composite exercises for futsal players. Consequently, one of the most important and important training aspects of the player's role during the game is characterized by alternating intense physical effort between fast and strong movements associated with skills and situations that require physical and skill adaptations according to the impact of the proposed training curriculum and to know the results of such These studies help to guide the number of young female players according to sound scientific methods.The sample of the research was chosen by lot, namely, the players of (Biladi) club for the season (2018-2019) and the number of (24) players, as they were divided into two groups (experimental and control) and random method (lottery) by (12) players for each group. These 23 exercises were implemented in the main section of the training unit within the duration of the special preparation for (8) weeks and (3) training units per week The total number of training modules (24) training units, the time of one training unit between (90) And the main section time (45) minutes,Data collection methods were used to facilitate the achievement of the research goal, and the most important results indicated that the combined exercises have a positive impact on the skills of the players of the experimental group has reached to identify the differences between the tests before and after the tests, and recommends the researcher to the need to adopt the combined exercises Training The exercises are designed to help develop the skills because of their positive impact on the performance of football players galleries.